Poetic Cinema and the Spirit of the Gift in the Films of Pabst, Parajanov, Kubrick and Ruiz - Jayamanne, Laleen (Book collections on Project MUSE., 2021)
Poetic Cinema and the Spirit of the Gift in the Films of Pabst, Parajanov, Kubrick and Ruiz explores the poetic thinking of these master filmmakers, expressed in several of their key films. It examines theoretical ideas, including Maori anthropology of the gift and Sufi philosophy of the image, to conceive film as abundant gift. Elaborating on how this gift may be received, this book imagines film as our indispensable mentor - a wild mentor who teaches us how to think with moving images by learning to perceive evanescent forms that simply appear and disappear. Bron: Flaptekst, uitgeversinformatie.